Prevalence Of Insomnia and Anxiety Among the Medical Students: Acrosectional Studyat Al-Kindy College of Medicine 2016 - Mohsin, Talib Saddam (Diyala Journal of Medicine, 2018)
Background: Medical student's population is believed to be at an increased risk for sleep deprivation. Therefore insomnia can be precipitated by or co-morbid with other psychiatric disorders including anxiety. Objective: To both insomnia and anxiety have negative professional and personal consequences, hence there's strong need to assess the prevalence of insomnia and anxiety. Patients and Methods: Across sectional study was conducted to all student in al-kindy college of medicine. The study was conducted from1stmarch to 1stmay 2016. 406 students were included in our study .Athens scale questionnaire for insomnia was used for assessing insomnia while Hamilton scale questionnaire was used to assess anxiety. Results: The prevalence of both insomnia and anxiety was (67.24%) it was higher in females, No.=173(72.6%) than males, No=100(59.5).There was significant association between insomnia and anxiety among the medical students should be recognized and attempts should be made to alleviate them to promote health among medical students of Al-kindy medical college. Conclusion: The prevalence of insomnia and anxiety were high among medical student and there was significant correlation between gender and both insomnia and anxiety. Females are more liable for developing insomnia and anxiety. The need for establishing clinical evaluation of insomnia and anxiety for proper management and care. Further studies among other colleges and societies are needed.